2014
DOI: 10.4236/aces.2014.41001
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation of Mercury from Used Silver Oxide Watch Batteries

Abstract: This paper deals with the reclamation of mercury from the used silver oxide quartz wristwatch batteries employing leaching-cementation technique. The used batteries are first crushed to liberate the encapsulated active material from the case which is leached in nitric acid to bring all metal contents into solution. After the removal of silver in the solution as silver chloride by precipitation, the mercury which is present as Hg 2+ in the solution has been reclaimed through cementation with zinc dust. Various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…On the other hand, organic acid production depends strongly on carbon and nitrogen sources. Mardad et al (2014) found that glucose as carbon source and (NH 4 ) 2 SO 4 as the nitrogen source, significantly increased tricalcium phosphate solubilization. Nitrogen source in the medium may lead to acidification or alkalinization, which in turn influences phosphorous availability (Plassard et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, organic acid production depends strongly on carbon and nitrogen sources. Mardad et al (2014) found that glucose as carbon source and (NH 4 ) 2 SO 4 as the nitrogen source, significantly increased tricalcium phosphate solubilization. Nitrogen source in the medium may lead to acidification or alkalinization, which in turn influences phosphorous availability (Plassard et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…In the past, mercury was also used in silver oxide batteries, but the new generation silver oxide batteries are mercury free. For this reason, mercury pollution is no longer a big concern for the recycling of waste silver oxide batteries. , Pyrometallurgical processes are utilized in some industrial practices due to their high efficiency and relatively simple procedures. However, pyrometallurgical processes usually require heavy investment for high temperature materials and facilities to capture toxic gases .…”
Section: Introductionmentioning
confidence: 99%
“…However, in Mexico there is no regulation for the maximum mercury and cadmium contents in these batteries, on the other hand there are no studies about the impact of these contaminants in the environment [3]. Research studies have been focused on leaching [4] [5], several have focused on silver and mercury recovering by precipitation [6] [7]. However, few studies have focused on silver recovery by liquid-liquid extraction.…”
Section: Introductionmentioning
confidence: 99%